VD_FINDINFO HC / 2010 / 630 vom 3. August 2010 - VD Tribunal cantonal (2010)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF | 324a CO, 337 al. 1 CO, 337 al. 2 CO, 337c al. 1 CO, 343 al. 3 CO, 444 CPC, 445 CPC, 451 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 456a CPC, 465 al. 1 CPC, 10 LJT, 46 al. 2 LJT, 46 LJT